Of religion and redemption: Evidence from default on Islamic loans - Baele, Lieven; Farooq, Moazzam; Ongena, Steven (Journal of Banking & Finance, 2014)
We compare default rates on conventional and Islamic loans using a comprehensive monthly dataset from Pakistan that follows more than 150,000 loans over the period 2006:04 to 2008:12. We find robust evidence that the default rate of Islamic loans is less than half the default rate of conventional loans. Islamic loans are less likely to default during Ramadan and in big cities if the share of votes to religious-political parties increases, suggesting that religion – either through individual piousness or network effects – may play a role in determining loan default.